Valley of decisions : biography and essays in honour of Hon. Justice Iorhemen Hwande, OFR, Chief Judge, Benue State. - Hwande, Iorhemen (Safari Books Ltd, 2012)
In a tribute to Hon. Justice Iorhemen Hwande CFR, Chief Judge of Benue State, this book includes contributions from a variety of scholars from Nigeria.
Keywords: Hwande, Iorhemen.; Law reform -- Nigeria.; Judicial process -- Nigeria.; Justice, Administration of -- Nigeria.; Judges -- Nigeria -- Benue State -- Biography.; Droit -- Réforme -- Nigeria.; Processus judiciaire -- Nigeria.; LAW -- Civil Procedure.; LAW -- Legal Services.; POLITICAL SCIENCE -- Government -- Judicial Branch.; Judges; Judicial process; Justice, Administration of; Law reform; Nigeria; Nigeria -- Benue State; Festschriften; Biographies; Festschriften.; Biographies.